McMinn's color atlas of human anatomy - Abrahams, Peter H; Hutchings, R. T; Marks, S. C (Mosby, 1998)
Revised to reflect the increasing emphasis on clinical anatomy and make this popular atlas more user-friendly. Sixty new dissection photographs have been added along with 250 clinical notes. Includes new layout, color-coded icons, and orientational diagrams. Previous edition: c1993. Hardcover, softcover available.
Keywords: Anatomy; anatomie